POLLen in the iCE: insights into the Adamello glacier (Italy) by pollen DNA and morphology - Cristofori, A.; Festi, D.; Bertoni, E.; Camin, F.; Pindo, M.; Vernesi, C.; Girardi, M.; Casarotto, C.; Varotto, C.; Maggi, V. (country:IT, 2018)
Glaciers were long studied as records of climatic variables, but information on the biological component is an emerging topic. Pollen, produced in large quantities by anemophilous plant species, can travel long distances and reach extreme habitats like glaciers. Thus, glaciers have the potential to log plant biodiversity through the pollen proxy. In order to verify the feasibility of the very first pollen DNA metabarcoding study on an alpine glacier, the deepest and widest Italian glacier was chosen, potentially archiving information dating back to the Little Ice Age. A 5.7 m ice core was retrieved from the Adamello glacier in March 2015. Ice core samples were cut in longitudinal sections and the following indicators were analyzed: thin sections, hydrogen and oxygen stable isotope ratios and pollen. Stable isotope ratios were measured using Isotope Ratio Mass Spectrometry. The pollen content of ice was analyzed by pollen DNA metabarcoding and classical light microscopy. Samples for DNA metabarcoding were concentrated, DNA was extracted, amplified with the trnL cpDNA barcode (c-h region, 140bp) and sequenced by a high throughput platform. Stable isotope ratios reveal a distinct pattern in the first two superficial meters of the ice core with a winter and summer season. Ice crystal structure transformation along the ice core was compared to stable isotope content, mass balance and pollen seasonality. The age of the ice core was estimated in 5 years. Pollen analysis recorded the presence of 34-55 pollen taxa, with an identification mostly at the species-level (60%) for DNA metabarcoding and a higher number of detected taxa for light microscopy analysis. The very first results on pollen DNA metabarcoding showed that environmental DNA archived in the glacier ice can be extracted, amplified and sequenced, indicating a good preservation of genetic material, even in a temperate glacier like Adamello. Pollen deposition in the ice of the glacier conserve a seasonal time-scale. Moreover, DNA-metabarcoding analyses allow an ...